VIOLENT CONFLICTS DYNAMICS IN POST-COLD WAR AFRICA: THE HUMAN SECURITY FACTOR - Luqman, A.B. (Farabi Journal of Social Sciences, 2025)
Through studying conflict transformation in Africa since the Cold War’s end, this paper looks at the dynamic nature of violent conflicts in Africa, as well as how human insecurities have impacted the conflicts. The study surveys literature on conflict trajectory in post-Cold War Africa and human security. Despite the reduction in interstate conflicts and an increase in intrastate conflicts in Africa, the character of the state cannot be seen to have displayed sensitivity to these changes. Failed state theory which explains inability to deliver political goods and services to the citizens by states is used for theoretically espousing violent conflicts dynamics and human insecurity influence on the conflicts, and attendant insecurity. Owing to state failure, human insecurities are significant contributors to post-Cold War conflicts in Africa. It is therefore suggested that African governments should prioritise welfare of their citizens, and protect them from existential threats and violence in the region. Keywords: Post-Cold War African conflict dynamics, human security, violent conflict, terrorism, failed state